2018
DOI: 10.3390/ijms19010155
|View full text |Cite
|
Sign up to set email alerts
|

LHCSR Expression under HSP70/RBCS2 Promoter as a Strategy to Increase Productivity in Microalgae

Abstract: Microalgae are unicellular photosynthetic organisms considered as potential alternative sources for biomass, biofuels or high value products. However, limited biomass productivity is commonly experienced in their cultivating system despite their high potential. One of the reasons for this limitation is the high thermal dissipation of the light absorbed by the outer layers of the cultures exposed to high light caused by the activation of a photoprotective mechanism called non-photochemical quenching (NPQ). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…PSII antenna size is inversely proportional to the time required for reaching 2/3 of the maximum fluorescence emission [33]. Oxygen evolution curves were performed as described [63]. Net oxygen production was calculated subtracting the oxygen consumption in the dark after each measurement at the different actinic lights.…”
Section: Table 2 Statistics Of the Mutations Found In E8 Mutant Strainmentioning
confidence: 99%
“…PSII antenna size is inversely proportional to the time required for reaching 2/3 of the maximum fluorescence emission [33]. Oxygen evolution curves were performed as described [63]. Net oxygen production was calculated subtracting the oxygen consumption in the dark after each measurement at the different actinic lights.…”
Section: Table 2 Statistics Of the Mutations Found In E8 Mutant Strainmentioning
confidence: 99%
“…Previous works demonstrated that C. reinhardtii npq4 mutant, which lacks both genes encoding for LHCSR3 protein, was characterized by a reduced NPQ phenotype, with the residual NPQ dependent on LHCSR1 subunit 18 , 27 . Indeed, the C. reinhardtii double mutant npq4 lhcsr1 , disrupted in all genes that encode for both LHCSR3 and LHCSR1 proteins, showed a null NPQ phenotype with high amounts of ROS formation and reduced growth rate 10 , 27 , 29 . Transcriptional analysis of C. reinhardtii cultures demonstrated that CO 2 concentration influences the expression of lhcSR1 and lhcSR3 ( lhcSR3.1 and lhcSR3.2 ) genes, which are respectively transcriptionally activated and downregulated at high CO 2 conditions 21 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Among photosynthetic organisms, microalgae have high potential with a wide range of applications of their biomass and its derivatives, from food/feed to biofuels and high-value products 1 – 9 . These unicellular organisms are characterized generally by a higher photosynthetic efficiency compared to higher plants due to the absence of non-photosynthetic tissues 10 , 11 . However, some bottlenecks need to be faced in order to improve their domestication process: in fact, their photosynthetic efficiency is far lower than the theoretical value, ranging between 1 and 3% on industrial scale 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations